Subcutaneous Trigeminal Nerve Field Stimulation for Refractory Facial Pain - Jakobs, Martin (J Vis Exp, 2017)
Chronic or neuropathic trigeminal facial pain can be challenging to treat. Neurosurgical procedures should be applied when conservative treatment fails. Neuromodulation techniques for chronic facial pain include deep brain stimulation and motor cortex stimulation, which are complex to perform. Subcutaneous nerve field stimulation is certified for chronic back pain and is the least invasive form of neuromodulation. We applied this technique to treat chronic and neuropathic trigeminal pain as an individual therapy concept. First, trial stimulation is performed. Subcutaneous leads are placed in the painful trigeminal dermatome under local anesthesia. The leads are connected to an external neurostimulator that applies constant stimulation. Patients undergo a 12 day outpatient trial to assess the effect of the stimulation. Electrodes are removed after the trial. If the patient reports pain reduction of at least 50% in intensity and/or attack frequency, a reduction in medication or increase in quality of life, permanent implantation is scheduled. New electrodes are implanted under general anesthesia and are subcutaneously tunneled to an infraclavicular internal pulse generator. Patients are able to turn stimulation on and off and to increase or decrease the stimulation amplitude as needed. This technique represents a minimal invasive alternative to other more invasive means of neuromodulation for trigeminal pain such as motor cortex stimulation or deep brain stimulation.